Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to find the values of these kind of summations:

$$\large\sum_{i=0}^6(6-i)\;\ast\;\sum_{j=1}^6(7-j)\;\ast\;\sum_{k=2}^7(8-k)\;\ast\;\sum_{\ell=3}^8(9-\ell)$$

share|cite|improve this question
    
@m.woj * means multiplication here. – Eight Jun 8 '12 at 6:49
    
abhinav8, Zev Thanks. (Question was: what does asterisk mean in that context?) – data Jun 8 '12 at 6:51
up vote 2 down vote accepted

Use that $$\begin{align}\sum_{t=a}^b(c-t)&=\left(\sum_{t=a}^bc\right)-\left(\sum_{t=a}^b t\right)\\\\&=\left(\sum_{t=a}^bc\right)-\left(\sum_{s=0}^{b-a} (s+a)\right)\\\\ &=\left(\sum_{t=a}^bc\right)-\left(\sum_{s=0}^{b-a} s\right)-\left(\sum_{s=0}^{b-a}a\right)\\\\ &=(b-a+1)c-(b-a+1)a-\left(\sum_{s=0}^{b-a} s\right)\\\\&=(b-a+1)(c-a)-\left(\sum_{s=0}^{b-a} s\right)\\\\&=(b-a+1)(c-a)-\frac{(b-a)(b-a+1)}{2}\\\\&=(b-a+1)(c-a-\tfrac{b}{2}+\tfrac{a}{2})\\\\&=(b-a+1)(c-\tfrac{b}{2}-\tfrac{a}{2})\end{align}$$ for each term. For example, $$\sum_{i=0}^6(6-i)=6+5+4+3+2+1=\fbox{21}=7\cdot 3=(6-0+1)(6-\tfrac{6}{2}-\tfrac{0}{2})\qquad\checkmark$$

share|cite|improve this answer
    
you seems to be wrong in last two steps of your equation, (c-a-(b/2)+(a/2)) should be equal to (c-(b/2)-(a/2)) but you have got (c-(b/2)+(a/2)).pls check and correct me if i am wrong. – Eight Jun 8 '12 at 6:43
    
@abhinav8: Thanks for catching that! You're correct, I made a careless error. I've edited my answer with the correct expression. – Zev Chonoles Jun 8 '12 at 6:45

Or the formula:

$$\sum_{i=k_1}^{k_2} (p-i) = (k_2-k_1+1)(p-\frac{1}{2}(k_1+k_2)).$$

share|cite|improve this answer
    
The answer to the original question is 194,481. – copper.hat Jun 8 '12 at 6:29

Hint: Use the following formula.

  • $\displaystyle \sum\limits_{i=1}^{n} i = \frac{n \cdot (n+1)}{2}$.

  • $\displaystyle \sum\limits_{i=0}^{6} (6-i) = \sum\limits_{i=0}^{6} (6 - i) = 6 \cdot \bigl(1+1+1+1+1+1+1\bigr)- \sum_{i=0}^{6} i =6 \times 7 - \frac{6 \cdot 7}{2}$

Similarly you can calculate the other summation's as well and then multiply them.

share|cite|improve this answer
    
Huh? How would that work in this case? – Gigili Jun 8 '12 at 6:09
    
@Gigili: I have edited my answer. – user9413 Jun 8 '12 at 6:12
    
Should the answer be $1+...+6 = 21$? – copper.hat Jun 8 '12 at 6:18
    
@copper.hat: Yeah. $21 = \frac{6 \cdot 7}{2}$ – user9413 Jun 8 '12 at 6:19
2  
I may be completely mistaken, but you value of $\sum_{i=0}^6 (6-i)$ seems completely wrong. Why would $i$ start first at 0 then 1? Why would $\sum_{i=1}^6 6 = 6 \cdot (1+2+3+4+5+6)$? – Najib Idrissi Jun 8 '12 at 6:28

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.